Determination of Employee Performance With Adaptability, Extraversion Personality, And Self-Efficacy - Syamsuri, Abd. Rasyid; Halim, Abd.; Siddik, Ega (TALENTA Publisher, Universitas Sumatera Utara, 2022)
Changes in the increasingly complex and competitive business environment require companies to be more responsive to survive and continue to grow. In supporting these changes, personal changes must be related to adaptability, extraversion personality, self-efficacy, and employee performance. As an employee, adaptability is needed to survive in industrial competition. Being able to adapt means responding to changes quickly and being responsible for a job. Having an extrovert personality can also create social interaction. Moreover, having confidence in one's abilities plays an important role in determining the goals. In addition, the abilities possessed by the employees can be correlated with the performance that they want to be achieved. This research was conducted in Gelora Plaza Medan City and Deli Serdang Regency, North Sumatra. The type of this research was explanatory and aimed to analyze the effect and correlation between variables. This research was conducted by distributing questionnaires as an instrument to collect data. The population and sample of this research involved 37 employees from Gelora Plaza Medan and 35 employees from Gelora Plaza Deli Serdang, with a total of 72 employees. This research used the saturation sampling technique to collect data by using all population members as a sample. The regression analysis results through partial and simultaneous tests prove that adaptability, extraversion personality, and self-efficacy have a significant and positive effect on employee performance. The coefficient results of determination proved that employee performance can be explained by adaptability, extraversion personality and self-efficacy of 57.6%